THE INFLUENCE OF SOCIAL MEDIA CONTENT ON INTENTION TO RECOMMEND THROUGH ONLINE ENGAGEMENT AS A MEDIATING VARIABLE ON MANDARIN LANGUAGE TEACHING CONTENT VIA INSTAGRAM FOR GENERATIONS Y AND Z IN INDONESIA - Kornelius, Stefani Mutiara; Antonio, Ferdi (FEB Universitas Sam Ratulangi Manado, 2024)
The aim of this research is to test and analyze the influence of social media content including the Language Style, Interesting Content, Useful Content and Unique Image Content Characteristic factors on Online Engagement as a mediator which then influences the Intention to Recommend factor after previously being influenced by Emotional Response of Language as a mediator to users of Mandarin language teaching content via Instagram XYZ to generations Y and Z in Indonesia. Testing of this research model, which was modified from previous research, was carried out quantitatively with survey data. Data was obtained from generations Y and Z in Indonesia who are followers of Instagram XYZ. This research method is a quantitative survey, with cross sectional data. Respondent data was taken using purposive sampling with a questionnaire distributed online. 178 samples were obtained that met the requirements for analysis using PLS-SEM. The research results show that the four social media content variables have a strong influence on Online Engagement activities, while the two strongest variables are Unique Image Content Characteristic and Useful Content. Then the Online Engagement factor which is moderated by the Emotional Response of Language factor is able to influence the Intention to Recommend of generations Y and Z in Indonesia.